2017
DOI: 10.1016/j.precisioneng.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of the probe tip based nanochannel scratching

Abstract: Copies of full items can be used for personal research or study, educational, or not-for-profit purposes without prior permission or charge. Provided that the authors, title and full bibliographic details are credited, a hyperlink and/or URL is given for the original metadata page and the content is not changed in any way. A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The possible reason is that in the scratching direction d2, the cutting tool is a pyramidal face rather than a blade, which leads to the material stack in front of the probe tip, as a result, the tip-sample interface is increased greatly, thus resulting in the reduction of scratching depth, this phenomenon has been found in the scratching simulation [29]. The scratching depth in the d1 direction is smaller than those in the d3/d4 directions, this may be caused by the assembly error of the probe.…”
Section: The Indentation Testmentioning
confidence: 96%
“…The possible reason is that in the scratching direction d2, the cutting tool is a pyramidal face rather than a blade, which leads to the material stack in front of the probe tip, as a result, the tip-sample interface is increased greatly, thus resulting in the reduction of scratching depth, this phenomenon has been found in the scratching simulation [29]. The scratching depth in the d1 direction is smaller than those in the d3/d4 directions, this may be caused by the assembly error of the probe.…”
Section: The Indentation Testmentioning
confidence: 96%
“…Researches have revealed that nanoscratching of hard-brittle materials is a complex process with multiple influencing factors, including scratch speed [6][7][8], shape and geometric parameters of tool [9,10], environment [11], and so on. In addition, many scholars have conducted studies to explore the effect of scratch directions in the processing of materials [12][13][14][15][16]. Yan investigated the material removal state under different scratch directions employing AFM on single crystal copper, it is found that the height of pile-up is greatly influenced by scratch directions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional macro positioning system, compliant micro/nano positioning system can realize nanometric resolution through the elastic deformation of flexure hinges, which has the advantages of no friction [7][8][9][10][11], no backlash, no lubrication and easy fabrication, whereas the travel range is usually limited from a few microns to several millimeters. In many application fields like probe tip-based micro/nano scratching, there have been quite a few demands of large stroke positioning [12][13][14], and many efforts have been devoted to realizing high precision and large workspace simultaneously. In order to compensate the positioning error of coarse actuator, the fine actuation part should have the ability to realize nanometric resolution in two perpendicular directions, and the motion stroke should be greater than the minimum resolution of coarse actuator, which is usually about several tens of microns.…”
Section: Introductionmentioning
confidence: 99%